Genomic characterization of two metagenome-assembled genomes of Tropheryma whipplei from China - Lv, Zhongdong; Chen, Yong; Zhou, Houqing; Chen, Zhonglin; Yao, Qianru; Ren, Jiali; Liu, Xianglu; Liu, Shuang; Deng, Xiaomei; Pang, Yingchen; Chen, Weijun; Yang, Huiling; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Whipple’s disease is a rare chronic systemic disease that affects almost any organ system of the body caused by the intracellular bacterium Tropheryma whipplei, which is found ubiquitously in the environment. Sequencing of the T. whipplei genome has revealed that it has a reduced genome (0.93 Mbp), a characteristic shared with other intracellular bacteria. Until our research started, 19 T. whipplei strains had been sequenced from cultures originated in France, Canada, and Germany. The genome of T. whipplei bacterium has not been studied in Asia yet. Here, two metagenome-assembled genomes (MAGs) of T. whipplei from China were reconstructed through metagenomic next-generation sequencing (mNGS) and genome binning. We also provided genomic insights into the geographical role and genomic features by analyzing the whole genome. The whole-genome phylogenetic tree was constructed based on single-nucleotide polymorphism (SNP) distance calculations and then grouped by distance similarity. The phylogenetic tree shows inconsistencies with geographic origins, thus suggesting that the variations in geographical origins cannot explain the phylogenetic relationships among the 21 T. whipplei strains. The two Chinese strains were closely related to each other, and also found to be related to strains from Germany (T. whipplei TW08/27) and France (T. whipplei Bcu26 and T. whipplei Neuro1). Furthermore, the Average Nucleotide Identity (ANI) matrix also showed no association between geographic origins and genomic similarities. The pan-genome analysis revealed that T. whipplei has a closed pan-genome composed of big core-genomes and small accessory genomes, like other intracellular bacteria. By examining the genotypes of the sequenced strains, all 21 T. whipplei strains were found to be resistant to fluoroquinolones, due to the genetic mutations in genes gyrA, gyrB, parC, and parE. The 21 T. Whipplei strains shared the same virulence factors, except for the alpC gene, which existed in 7 out of the 21 T. whipplei strains. When comparing 21 entire T. whipplei pan-genomes from various nations, it was discovered that the bacterium also possessed a closed genome, which was a trait shared by intracellular pathogens.